2023
DOI: 10.3390/md21050315
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Molecular Characterization of Fucoidan Isolated from Ascophyllum nodosum Brown Seaweed Grown in Ireland

Abstract: The present study investigates the molecular characteristics of fucoidan obtained from the brown Irish seaweed Ascophyllum nodosum, employing hydrothermal-assisted extraction (HAE) followed by a three-step purification protocol. The dried seaweed biomass contained 100.9 mg/g of fucoidan, whereas optimised HAE conditions (solvent, 0.1N HCl; time, 62 min; temperature, 120 °C; and solid to liquid ratio, 1:30 (w/v)) yielded 417.6 mg/g of fucoidan in the crude extract. A three-step purification of the crude extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Moreover, Sellimi et al [35] observed the highest reducing activity of Gongolaria barbata fucoidan at concentrations of 1 mg/mL and 24.62 mg ascorbic acid equivalents/g of the sample. Correlating with our results, Rajauria et al [44] reported FRAP values for A. nodosum crude fucoidan and commercial fucoidan from F. vesiculosus to be 38.6 and 13.9 mg TE/g, respectively. The reducing capacities of fucoidans are supposed to be due not only to their sulfate content and molecular weight but also to the presence of hydroxyl and carboxylic groups of the uronic acids in their chain [15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, Sellimi et al [35] observed the highest reducing activity of Gongolaria barbata fucoidan at concentrations of 1 mg/mL and 24.62 mg ascorbic acid equivalents/g of the sample. Correlating with our results, Rajauria et al [44] reported FRAP values for A. nodosum crude fucoidan and commercial fucoidan from F. vesiculosus to be 38.6 and 13.9 mg TE/g, respectively. The reducing capacities of fucoidans are supposed to be due not only to their sulfate content and molecular weight but also to the presence of hydroxyl and carboxylic groups of the uronic acids in their chain [15].…”
Section: Discussionsupporting
confidence: 91%
“…The higher scavenging effect of Gongolaria barbata fucoidan compared to Ericaria crinita , Cystoseira compessa , and Ericaria sedoides fucoidan could be related to its higher content of sulfate groups. Fucoidans isolated from Cystoseira / Eicaria / Gongolaria species resulted to be more effective radical scavenging agents compared to other brown algae such as Ascophyllum nodosum (43.0%, IC 50 = 1.16 mg/mL) [ 44 ], Undaria pinnatifida (86.80% at concentration 1 mg/mL) [ 45 ], Sargassum pallidum (19.1%), S. vulgare (22.5%), and S. tenerrimum (64.66%) at concentrations of 2.5 mg/mL, 3.8 mg/mL, and 1 mg/mL, respectively [ 15 ]. Compared to crude fucoidans, the established lower scavenging effect of the commercial fucoidan from F. vesiculosus (IC 50 = 1.66 mg/mL), also reported by other authors (IC 50 = 2.30 mg/mL [ 44 ]; 76.61% at 4 mg/mL [ 46 ]), could be related to its higher purity and the absence of residual substances such as phenols, pigments, and proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies performed in other types of algae, fucoidan content has also been determined. Thus, fucoidan extracted from Ascophyllum nodosum using a MWCO of 10 kDa showed a content of 562.3 ± 0.08 mg/g of dry seaweed extract [ 33 ]. Another report on Padina boryana showed a fucoidan content of 1.59 ± 0.16%, expressed in dry weight, in an extract obtained by using a 10 kDa MWCO fractionation [ 34 ].…”
Section: Resultsmentioning
confidence: 99%